Pengembangan media pembelajaran virtual reality (VR) untuk mengenalkan budaya lokal Malang ke pembelajar BIPA - Muzaki, Helmi; Susanto, Gatut; Andajani, Kusubakti; Widyartono, Didin; Akhsani, Ilham; Moorthy, Thilip Kumar (Universitas Mulawarman, 2025)
Learning Indonesian for Foreign Speakers (BIPA) is closely related to cultural learning. Language acquisition requires not only fluency, but also an understanding of its cultural context. However, introducing culture to BIPA learners, especially through traditional media, such as images or textbooks, can make learning less effective and interesting. This study aimed to develop virtual reality (VR)-based learning media to introduce local Malang culture to foreign speakers. This study used the four-stage development method designed by Thiagarajan. Four stages are defined: design, development, and dissemination. The VR media were validated by BIPA experts and tested on seven learners from China, Taiwan, Vietnam, and Yemen. The product trial results show that the visual and audio quality received a score of (81.6), ease of use (80), VR's ability to provide a realistic experience of Malang cultural life (84), VR's ability to increase interest in learning Indonesian culture (85), VR's ability to increase cultural knowledge (82.5), suitability to needs (81.2), and VR's effectiveness as a cultural learning medium (82.5). This study confirms that VR is an engaging and effective tool for introducing local culture to BIPA students in line with their needs and expectations, especially those who are familiar with immersive technology.